2012
DOI: 10.3390/en5114804
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Bidding Strategies for Wind Power Producers in the Day-ahead Electricity Market

Abstract: Wind Power Producers (WPPs) seek to maximize profit and minimize the imbalance costs when bidding into the day-ahead market, but uncertainties in the hourly available wind and forecasting errors make the bidding risky. This paper assumes that hourly wind power output given by the forecast follows a normal distribution, and proposes three different bidding strategies, i.e., the expected profit-maximization strategy (EPS), the chance-constrained programming-based strategy (CPS) and the multi-objective bidding st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A wind farm, as an economic agent, participates in the electricity market to make profit [8]. In order to maximize its profit, it adopts bidding strategies.…”
Section: Problem Statementmentioning
confidence: 99%
“…A wind farm, as an economic agent, participates in the electricity market to make profit [8]. In order to maximize its profit, it adopts bidding strategies.…”
Section: Problem Statementmentioning
confidence: 99%
“…This was the case in this research. A lot of work has been done in a field of bidding curve optimization models and a review of these models can be found in [11], with some early works in [12][13][14].…”
Section: Open Accessmentioning
confidence: 99%
“…With the increasing penetration of wind energy into power grids, the negative influences of wind farms are non-negligible [1,2]. The variability and intermittence of wind power cause fluctuation of the voltage and frequency of the grid, affecting the safety of the power grid [3,4].…”
Section: Introductionmentioning
confidence: 99%